RIC-3 exclusively enhances the surface expression of human homomeric 5-hydroxytryptamine type 3A (5-HT3A) receptors despite direct interactions with 5-HT3A, -C, -D, and -E subunits - Walstab, Jutta; Hammer, Christian; Lasitschka, Felix; Möller, Dorothee; Connolly, Christopher N.; Rappold, Gudrun; Brüss, Michael; Bönisch, Heinz; Niesler, Beate (The journal of biological chemistry, 2010)
Although five 5-hydroxytryptamine type 3 (5-HT3) subunits (A-E) have been cloned, knowledge on the regulation of their assembly is limited. RIC-3 has been identified as a chaperone specific for the pentameric ligand-gated nicotinic acetylcholine and 5-HT3 receptors. Therefore, we examined the impact of RIC-3 on differently composed 5-HT3 receptors with the focus on 5-HT3C, -D, and -E subunits. The influence of RIC-3 on these receptor subtypes is supported by the presence of RIC3 mRNA in tissues expressing at least one of the subunits 5-HT3C, -D, and -E. Furthermore, immunocytochemical studies on transfected mammalian cells revealed co-localization in the endoplasmic reticulum and direct interaction of RIC-3 with 5-HT3A, -C, -D, and -E. F ...
Im Titel erscheint bei dem Ausdruck (5-HT3A) die Ziffer 3 tiefgestellt
Gesehen am 04.10.2023